2003
DOI: 10.1074/jbc.m300660200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Catalytic Domain of the PknB Serine/Threonine Kinase from Mycobacterium tuberculosis

Abstract: With the advent of the sequencing programs of prokaryotic genomes, many examples of the presence of serine/threonine protein kinases in these organisms have been identified. Moreover, these kinases could be classified as homologues of those belonging to the well characterized superfamily of the eukaryotic serine/threonine and tyrosine kinases. Eleven such kinases were recognized in the genome of Mycobacterium tuberculosis. Here we report the crystal structure of an active form of PknB, one of the four M. tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(193 citation statements)
references
References 37 publications
11
181
1
Order By: Relevance
“…M. tuberculosis PknB kinase domain (1o6y) (28) and phosphorylase kinase (Phk)-peptide substrate complex (2phk) (29) crystal structures were aligned using PyMOL (DeLano Scientific) to add missing PknB-peptide contact residues in the activation loop. Activation loop residues from Phk and its substrate were changed to the corresponding PknB and peptide substrate residues so that this model should represent the conformation of the active form of PknB.…”
Section: Methodsmentioning
confidence: 99%
“…M. tuberculosis PknB kinase domain (1o6y) (28) and phosphorylase kinase (Phk)-peptide substrate complex (2phk) (29) crystal structures were aligned using PyMOL (DeLano Scientific) to add missing PknB-peptide contact residues in the activation loop. Activation loop residues from Phk and its substrate were changed to the corresponding PknB and peptide substrate residues so that this model should represent the conformation of the active form of PknB.…”
Section: Methodsmentioning
confidence: 99%
“…However, these eukaryotic-like protein kinases lack some of the essential motifs of ePKs. Other studies have indicated that some of the eukaryotic-like protein kinases had distinct evolutionary histories, which might be even more ancient than ePKs (9,25).…”
Section: Discussionmentioning
confidence: 99%
“…Despite sequence identity less than 27%, prokaryotic and eukaryotic serine/threonine kinases show close conformational similarity [7,11,17]. The conformational changes in activation of these kinases with a characteristic two-lobed structure are linked to changes at regulatory sites that include phospho-acceptors in the activation loop (Fig.…”
Section: Site-directed Mutagenesis Of Ser-71 Ser-128 Thr-168 and Thmentioning
confidence: 99%